Policy learning from evidence during polycrises: a case of EU environmental policy - Bishoy Zaki; Valérie Pattyn; Ellen Wayenberg (Policy Design and Practice)
Despite their increasing frequency and magnitude, research on how polycrises influence policymaking has been remarkably scarce. In this article, we approach this issue from an evidence-based policy learning perspective. We explore how the polycrisis involving the progressive intersections between the climate change crisis, the COVID-19 pandemic, and the energy crisis influenced evidence-based policy learning underlying the European Union’s climate policymaking. Our findings show that at the initial phases of the polycrisis, interdisciplinary scientific evidence was employed to depoliticize the climate change crisis and facilitate a paradigmatic policy shift. Yet, as relatively faster burning crises overlapped, such evidence played an increasingly substantiating role for previously established institutional choices, and then its role further diminished as more crises overlapped. These findings offer a more robust theoretical understanding of evidence-based policy learning and its contribution to policy change within polycrises. This also draws practitioners’ attention to the need for actively re-aligning evidence-based policy learning practices as political conditions evolve during polycrises.